Peningkatan Literasi Digital dan Keuangan Siswa SMP Negeri 01 Tanjungsiang Menuju Generasi Melek Teknologi dan Finansial - Giantomi Muhammad; Ayi Sobarna; Safitri A, Nabila; Faujiah, Chicha Siti; Putri, Rachma Vidia (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
At SMP Negeri 1 Tanjungsiang, a digital and financial literacy program has been created to prepare students to face these challenges by understanding the use of technology and managing personal finances. This is because digital and financial literacy are important skills for students in the modern era which is characterized by rapid technological developments and global economic complexity. The goal of the program is to teach students how to properly use digital tools, know about cybersecurity, and properly control personal finances. Preliminary results show that students understand both areas better. However, limited technological infrastructure, differences in students' and teachers' prior knowledge, and lack of community support are some of the problems that hinder these programs. The success of this program and its long-term impact on preparing students for the digital era and future economy is critical.